2016
DOI: 10.21010/ajtcam.v13i4.16
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Tulbaghia Violacea Harv. In a Diabetic Model.

Abstract: Background: Diabetes mellitus (DM) is a cluster of metabolic diseases with chronic hyperglycemia as a defining feature, associated with long-term organ damage and dysfunction. In this study we examined the effect of Tulbaghia violacea rhizome methanolic extract on blood glucose and lipids in normal and streptozotocin-induced diabetic rats. Materials and Methods: Male Wistar rats (250-300g) were injected intraperitoneally (i.p.) with streptozotocin (60mg/kg body weight) to induce diabetes; or provided with dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In streptozotocin diabetes-induced rat models, T. violacea attenuated diabetes-associated physiological conditions resulting in improved body weights, reduced fasting blood glucose levels, enhanced glucose tolerance and significantly elevated plasma insulin and liver glycogen content [96]. These data were corroborated in another study in which T. violacea noticeably reduced blood glucose and serum lipid (triglyceride (TG), total cholesterol (TC), and very low-density lipoprotein (VLDL)) levels while raising plasma insulin in a streptozotocin-induced diabetic rat model [97]. In an assessment for negating cardiovascular associated conditions, T. violacea in in vivo models markedly reduced systolic blood pressure (BP), diastolic BP, mean arterial pressure (MAP) and the heart rate in both ageinduced and spontaneous hypertensive rats [98].…”
Section: Antioxidant Activitymentioning
confidence: 66%
“…In streptozotocin diabetes-induced rat models, T. violacea attenuated diabetes-associated physiological conditions resulting in improved body weights, reduced fasting blood glucose levels, enhanced glucose tolerance and significantly elevated plasma insulin and liver glycogen content [96]. These data were corroborated in another study in which T. violacea noticeably reduced blood glucose and serum lipid (triglyceride (TG), total cholesterol (TC), and very low-density lipoprotein (VLDL)) levels while raising plasma insulin in a streptozotocin-induced diabetic rat model [97]. In an assessment for negating cardiovascular associated conditions, T. violacea in in vivo models markedly reduced systolic blood pressure (BP), diastolic BP, mean arterial pressure (MAP) and the heart rate in both ageinduced and spontaneous hypertensive rats [98].…”
Section: Antioxidant Activitymentioning
confidence: 66%
“…It is a bulbous plant that is characterised by hairless leaves arising from a white fleshy stalk, purple flowers, and a distinctive odour similar to Allium sativum when the leaves or rhizome are crushed. The plant has been used traditionally to treat ailments such as headaches, fever, constipation, rheumatism, heart problems, chest problems, fits, and paralysis [90][91][92][93]. Madike et al [94] reported on the phytochemical screening of the aqueous leaf and bulb extracts of T. violacea and showed the presence of saponins, cardiac glycosides, coumarins, terpenoids, proteins, flavonoids, and phenols.…”
Section: Tulbaghia Violaceamentioning
confidence: 99%